Islamic democratic discourse theory, debates, and philosophical perspectives - Khan, M. A. Muqtedar (Lexington Books, 2006)
This wide-ranging set of essays explores the multi-faceted relationship between Islam and democracy. Each essayist's unique viewpoint on contemporary Islam provides insight into Islamic political thought and its connection to Western democracy.